In search of novel highly active mitochondria‐targeted antioxidants: Thymoquinone and its cationic derivatives. Issue 13 (10th May 2013) - Severina, Inna I.; Severin, Fedor F.; Korshunova, Galina A.; Sumbatyan, Natalya V.; Ilyasova, Tatyana M.; Simonyan, Ruben A.; Rogov, Anton G.; Trendeleva, Tatyana A.; Zvyagilskaya, Renata A.; Dugina, Vera B.; Domnina, Lidia V.; Fetisova, Elena K.; et al.
Abstract : Since the times of the Bible, an extract of black cumin seeds was used as a medicine to treat many human pathologies. Thymoquinone (2‐demethylplastoquinone derivative) was identified as an active antioxidant component of this extract. Recently, it was shown that conjugates of plastoquinone and penetrating cations are potent mitochondria‐targeted antioxidants effective in treating a large number of age‐related pathologies. This review summarizes new data on the antioxidant and some other properties of membrane‐penetrating cationic compounds where 2‐demethylplastoquinone substitutes for plastoquinone. It was found that such a substitution significantly increases a window between anti‐ and prooxidant concentrations of the conjugates. Like the original plastoquinone derivatives, the novel compounds are easily reduced by the respiratory chain, penetrate through model and natural membranes, specifically accumulate in mitochondria in an electrophoretic fashion, and strongly inhibit H2 O2 ‐induced apoptosis at pico‐ and nanomolar concentrations in cell cultures. At present, cationic demethylplastoquinone derivatives appear to be the most promising mitochondria‐targeted drugs of the quinone series.